2012
DOI: 10.1124/jpet.112.194027
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of (3S)-3-(Hydroxymethyl)-4-(5-Methylpyridin-2-yl)-N-[6-(2,2,2-Trifluoroethoxy)pyridin-3-yl]-3,4-Dihydro-2H-Benzo[b][1,4]Oxazine-8-Carboxamide (JTS-653), a Novel Transient Receptor Potential Vanilloid 1 Antagonist

Abstract: Transient receptor potential vanilloid 1 (TRPV1) activation in peripheral sensory nerve is known to be associated with various pain-related diseases, thus TRPV1 has been the focus as a target for drug discovery. In this study, we characterized the pharmacological profiles of (3S) -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…Nilius and Szallasi point at 2 compounds, PHE377 and JTS‐653, as potential exceptions, but do not support their claim with data. The polymodal antagonist JTS‐653 has been reported to potently block proton‐induced activation of both rat and human TRPV1 channels and to cause hyperthermia in rats; therefore, it fully fits the proposed model. As for PHE377, no data regarding this compound have been published in the peer‐reviewed literature.…”
Section: Discussionsupporting
confidence: 56%
“…Nilius and Szallasi point at 2 compounds, PHE377 and JTS‐653, as potential exceptions, but do not support their claim with data. The polymodal antagonist JTS‐653 has been reported to potently block proton‐induced activation of both rat and human TRPV1 channels and to cause hyperthermia in rats; therefore, it fully fits the proposed model. As for PHE377, no data regarding this compound have been published in the peer‐reviewed literature.…”
Section: Discussionsupporting
confidence: 56%
“…JTS‐653 (Fig. ) has been studied for the potential treatment of postherpetic neuralgia (phase II completed) and overactive bladder pain (Phase II discontinued) . XEN‐D0501 (chemical structure not disclosed) entered clinical development for the indications of chronic cough and COPD (phase II completed, http://ClinicalTrials.gov Identifier: NCT02233699, NCT02233686).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…TRPV1 channels play an important role in inflammatory mechanical allodynia (Gavva et al ., ; Yu et al ., ; Hillery et al ., ; Kitagawa et al ., ). On testing LE135 in a model of mechanical allodynia, using the von Frey method (Caterina et al ., ; Petrus et al ., ), we found that intraplantar injection of LE135 substantially reduced the mechanical threshold of the injected hindpaws.…”
Section: Resultsmentioning
confidence: 97%